Associations of Demographic Factors and Tobacco Use With Progesterone and Estradiol During Pregnancy - Kristin Ashford PhD; Emily Rayens BS, BA; Amanda T. Wiggins PhD; Mary Kay Rayens PhD; Molly Malany Sayre PhD; John O'Brien MD (SAGE Publishing, 2018)
Objective To evaluate the association of biochemically validated prenatal tobacco use with serum progesterone and estradiol in the second trimester of pregnancy, controlling for demographic and personal factors. Study design This secondary analysis of a multicenter longitudinal study included 114 women with singleton pregnancies. Multiple regression analysis assessed whether prenatal tobacco use was related to hormone levels during the second trimester, controlling for covariates (age, body mass index, and race or ethnicity, with gestational age added to subsequent models). Result In the initial regressions, tobacco users had significantly lower progesterone level compared with nonsmokers ( p  = .037), while estradiol was unrelated to prenatal tobacco use. Women with greater body mass index also had significantly lower progesterone ( p  = .028), but body mass index was unrelated to estradiol. With gestational age as an additional covariate, prenatal tobacco use was no longer a significant predictor of progesterone, but both body mass index and gestational age were significant ( F  = 10.6, p  < .001, R 2  = 0.35). For estradiol, the overall regression of estradiol on age, body mass index, and race or ethnicity was not significant ( F  = 1.2, p  = .31). With gestational age added to the model, the overall model was significant ( F  = 7.2, p  < .001, R 2  = 0.27). Conclusion This study provides additional evidence that prenatal tobacco use may influence lower serum progesterone during the second trimester. This is of particular concern given the link between depressed progesterone activity and risk for preterm birth.